ANALYSIS OF HUMAN CAPITAL READINESS AND DIGITAL CULTURE ON EMPLOYEE PERFORMANCE IN FACING INDUSTRY 4.0: CASE OF PERUM DAMRI - Eka Febriani, Nabila
Technological advancements in the Industry 4.0 era have transformed the way companies operate, presenting both opportunities and challenges. For Perum DAMRI, adapting to these changes requires a strategic focus on enhancing human capital readiness and fostering a strong digital culture to improve employee performance. Employee performance is a critical factor in achieving organizational productivity and goals, yet the process of transformation is hindered by insufficient employee readiness and weak digital capabilities. This study aims to examine the impact of human capital readiness and digital culture on employee performance in the context of Industry 4.0. It explores key dimensions of employee readiness, including skills, knowledge, and attitudes, alongside digital culture elements such as innovation, data-driven decision-making, collaboration, open culture, digitalfirst mindset, agility, flexibility, and customer centricity. A mixed-method approach was employed, combining quantitative data from questionnaires distributed to 103 employees and qualitative insights from interviews with the Organization Development and Human Capital divisions. The findings reveal a significant influence of human capital readiness and digital culture on employee performance. However, the Human Development Index (HDI) assessment highlights gaps in the knowledge and hard skills dimensions, indicating insufficient organizational understanding and preparedness for Industry 4.0. Additionally, the digital culture analysis identified weaknesses in innovation, customer centricity, and collaboration compared to other dimensions. This study proposes actionable strategies to enhance employee performance, including targeted seminars and workshops on digital technology, as well as implementing a combined top-down and bottom-up approach by integrating a "Digital DNA" into the organization's culture. These recommendations aim to strengthen Perum DAMRI’s human capital readiness and cultivate a robust digital culture, ensuring organizational resilience and competitiveness in the Industry 4.0 era.